Gender and Uveitis in Patients with Multiple Sclerosis - Lynn K. Gordon; Debra A. Goldstein (Journal of Ophthalmology)
Multiple sclerosis (MS), a demyelinating disease of the central nervous system, is more commonly seen in women. It has been associated with both anterior and intermediate uveitis as well as retinal vasculitis. Ocular inflammation may develop concurrent with, prior to, or after the development of neurologic signs and symptoms. Patients with MS have an approximately 1% chance of developing intraocular inflammation. Patients with intermediate uveitis have an 8–12% risk of being diagnosed with MS. This risk is higher in females and in those with bilateral disease. This should be kept in mind when evaluating patients with uveitis, particularly in those patients for whom TNF inhibitor therapy is being considered, as these agents may worsen demyelinating disease.